(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Competition between maize (Zea mays L.) and weeds is aserious challenge to crop production. A field study was conducted at theDemonstration Farm, Faculty of Agriculture, University of Khartoum,Sudan, during 2008/09 and 2009/10 winter seasons, to determine themagnitude of yield losses due to weed competition and identify thecritical period of weed interference in maize. The experiment consisted oftwo sets. In the first set the crop was kept weed-free for 0, 2, 4, 6, and 8weeks after sowing. In the second set weeds were allowed to competewith the crop for 0, 2, 4, 6, and 8 weeks after sowing. Unrestricted weedgrowth reduced maize cob length, cob weight, grain number/ plant, 100seeds weight and grain weight/ plant by 62%, 82%, 75%, 49% and 87%,respectively in the 2008/2009 season and by 62%, 89%, 75%, 41% and85%, respectively in the 2009/2010 season. The presence of weedsthroughout the crop growth duration resulted in 82% and 84% loss ingrain yield in seasons 2008/09 and 2009/10, respectively. The criticalperiod of weed control in maize was found to be between 2 and 6 weeksafter sowing